What determines family structure? - David M. Blau; Wilbert van der Klaauw (Institute for the Study of Labor (IZA), 2010)
We estimate the effects of policy and labor market variables on the fertility, union formation and dissolution, type of union (cohabiting versus married), and partner choices of the NLSY79 cohort of women. These demographic behaviors interact to determine the family structure experienced by the children of these women: living with the biological mother and the married or cohabiting biological father, a married or cohabiting step father, or no man. We find that the average wage rates available to men and women have substantial effects on family structure for children of black and Hispanic mothers, but not for whites. The tax treatment of children also affects family structure. Implementation of welfare reform and passage of unilateral divorce laws had much smaller effects on family structure for the children of this cohort of women, as did changes in welfare benefits. The estimates imply that observed changes from the 1970s to the 2000s in the policy and labor market variables considered here contributed to a reduction in the proportion of time spent living without a father by children of the NLSY79 cohort of women. This suggests that the observed increase in this non-traditional family structure in the U.S. in the last three decades was caused by other factors.
Keywords: J12; 330; Family structure; Familiensoziologie; Lohnniveau; Familienleistungsausgleich; Familienrecht; USA